2022
DOI: 10.3390/foods11040597
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Salt and Salicornia herbacea L. on Physiochemical, Nutritional, and Quality Parameters for Extending the Shelf-Life of Semi-Dried Mullets (Chelon haematocheilus)

Abstract: Mullet, a coastal fish species, is commonly used as a salted dried fish in many countries, including Korea, Japan, and the southeastern United States. The purpose of this investigation was to develop high-quality products of salted semi-dried mullet (SSDM) using natural salt and Salicornia herbacea L. (SAL). The antioxidant activity of SAL was investigated by in vitro studies. The physicochemical and nutritional characteristics of fresh mullet (FM), salted control (SSDM-CON), and SAL-treated (SSDM-SAL) mullet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The results obtained with the present study indicate that no experimental group (fresh mullet (FM) and salted semidried mullet (SSDM)) had Staphylococcus aureus . This indicates that the semidried salted method followed by using natural salt and S. herbacea treatment for preservation purpose is capable of preventing microbial contamination and prolonging shelf life [ 104 ].…”
Section: Nutrition Profile and Health Impactsmentioning
confidence: 99%
“…The results obtained with the present study indicate that no experimental group (fresh mullet (FM) and salted semidried mullet (SSDM)) had Staphylococcus aureus . This indicates that the semidried salted method followed by using natural salt and S. herbacea treatment for preservation purpose is capable of preventing microbial contamination and prolonging shelf life [ 104 ].…”
Section: Nutrition Profile and Health Impactsmentioning
confidence: 99%
“…TBARS values did not differ across different treatments and were in the range of those found by Jin et al [ 46 ] in dry-cured bacon (i.e., from 0.2 to 0.4). In addition, Jo et al [ 44 ] obtained a similar relation for TBARS values in a different type of product with GP. The potential antioxidant effect of GP mentioned by previous authors [ 47 , 48 ] could not be observed either in the dry-cured pork bellies from this study, or in those from that study [ 44 ].…”
Section: Resultsmentioning
confidence: 70%
“…In addition, Jo et al [ 44 ] obtained a similar relation for TBARS values in a different type of product with GP. The potential antioxidant effect of GP mentioned by previous authors [ 47 , 48 ] could not be observed either in the dry-cured pork bellies from this study, or in those from that study [ 44 ]. This effect might perhaps be seen after longer storage periods.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…An increased antioxidant activity (with similar microbial quality) and reduced sodium content were reported when white cabbage ( Brassica oleracea ) was fermented with fresh Salicornia shoots as a salt substitute for table salt (Pires‐Cabral et al., 2021). Furthermore, Salicornia shoot extract was able to extend the shelf life and quality of semi‐dried mullets ( Chelon haematocheilus ), compared to the mullets preserved with table salt, and it also increased the antioxidant activity and conserved the nutrient profile due to decreased denaturation of crude proteins and fats, including essential polyunsaturated fatty acids and omega‐3 fatty acids while giving a pleasant meat color, which is important for consumer acceptance (H. Jo et al., 2022). Although there are different ways to consume Salicornia (e.g., raw, boiled, stir‐fried, etc.…”
Section: Salicornia: a Plant With A Range Of Benefitsmentioning
confidence: 99%